Observation of ψ 3686 → K − Λ 1520 Ξ ¯ + $$ ψ (3686)→ K^{-}Λ (1520){\overline{Ξ}}^{+} $$ + c.c. - The BESIII collaboration; M. Ablikim; M. N. Achasov; P. Adlarson; O. Afedulidis; X. C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; et al. (Journal of High Energy Physics)
Abstract Based on (2712.4 ± 14.3) × 106 ψ(3686) events collected at the BESIII detector operating at the BEPCII collider, we present the first observation of the decay ψ 3686 → K − Λ 1520 Ξ ¯ + $$ \psi (3686)\to {K}^{-}\Lambda (1520){\overline{\Xi}}^{+} $$ + c.c.. The product branching fraction B ψ 3686 → K − Λ 1520 Ξ ¯ + + c . c . × B Λ 1520 → p K − $$ \mathcal{B}\left[\psi (3686)\to {K}^{-}\Lambda (1520){\overline{\Xi}}^{+}+\textrm{c}.\textrm{c}.\right]\times \mathcal{B}\left[\Lambda (1520)\to p{K}^{-}\right] $$ is measured to be (9.47 ± 0.75 ± 0.97) × 10 −7, where the first uncertainty is statistical and the second systematic.